The Benefits of Cancer Genetic Panel Testing in At-Risk Women: A Single Institution Experience [24M]. (May 2018) - Frost, Anja S. H.; Toaff, Miriam C.; Biagi, Tara; Stark, Elizabeth; McHenry, Allison; Kaltman, Rebecca
Abstract : INTRODUCTION: The scope of panel testing for hereditary cancer syndromes is expanding rapidly. We sought to evaluate the role of panel testing in identifying actionable genetic mutations in high-risk or affected women, beyond BRCA-limited testing. METHODS: A retrospective chart review was conducted of all patients presenting to a multi-disciplinary cancer program at George Washington University for genetic counseling from 1/2015 and 12/2016. The results of testing and management implications, based on NCCN guidelines, were recorded. RESULTS: Of 673 patients that underwent single site, BRCA-limited, or panel testing, 17% (n=116) were found to have at least one deleterious mutation, of which 96% (n=111) had changes in clinical management. Over one half (65%, n=65) of patients who tested positive for a mutation had undergone panel testing and three-quarters (n=49) of those individuals were diagnosed with non-BRCA mutations. The latter group represents patient's whose mutations would have been missed without a broader panel test. Ninety-six percent of those testing positive for a mutation (n=111) had significant increase in clinical surveillance and/or management. All of the true negative individuals (n=45) were able to decrease their surveillance and/or management. CONCLUSION: Despite concern that the results of panel testing do not translate into clinically impactful management of high-risk individuals, our data indicates that guideline-based management is frequently altered by such testing. Obstetrician-gynecologists should incorporate detailed family histories into their routine visits, and counsel patients on the availability and utility of genetic panel testing when appropriate.